The role of network modifiers in the creation of photoluminescence in CaTiO3 - Pontes, F. M.; Pinheiro, C. D.; Longo, Elson [UNESP]; Leite, E. R.; de Lazaro, SR; Varela, José Arana [UNESP]; Pizani, P. S.; Boschi, T. M.; Lanciotti, F. (Elsevier B.V., 2003)
We discuss the nature of visible photoluminescence (PL) at room temperature in amorphous calcium titanate in the light of the results of recent experimental and quantum mechanical theoretical studies. Our investigation of the electronic structure involved the use of first-principle molecular calculations to simulate the variation of the electronic structure in the calcium titanate crystalline phase, which is known to have a direct band gap, and we also made an in-depth examination of amorphous calcium titanate. The results of our theoretical calculations of amorphous calcium titanate indicate that the formation of fivefold coordination in the amorphous system may introduce delocalized electronic levels in the highest occupied and the lowest unoccupied molecular orbitals. These delocalized electronic levels are related to the formation of a tail in the absorbance spectrum curve. The results indicate that amorphous calcium titanate has the conduction band near the band gap dominated by Ca states contribution. Experimental optical absorption measurements showed the presence of a tail. These results are interpreted by the nature of these exponential optical edges and tails, associated with defects promoted by the disordered structure of the amorphous material. We associate them with delocalized states in the band gap. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: photoluminescence; calcium titanate; absorbance spectrum